2022
DOI: 10.3389/fpubh.2022.876298
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Health and Sleep Quality of Medical Graduates During the Second Wave of COVID-19 Pandemic in Post-epidemic Era

Abstract: Recently, a COVID-19 virus variant spread rapidly in Guangzhou, China, causing public panic. This study aimed to understand the psychological and sleep-related consequences of the secondary outbreak of the pandemic on medical students. In this cross-sectional survey-based study, participants anonymously completed structured questionnaires online from June 8–22, 2021. We collected participants' demographic and general information. Anxiety, depression, and sleep quality were measured using the Zung Self-Rating A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
7
2
Order By: Relevance
“…This was consistent with the results of another survey ( 48 ) on anxiety and depression symptoms of overseas medical students during the COVID-19 pandemic. In contrast to another study ( 36 ), the effect of being a single-child on adverse emotions status was not significant in this study. The reason for this discrepancy may be due to the different regions in which the study was conducted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was consistent with the results of another survey ( 48 ) on anxiety and depression symptoms of overseas medical students during the COVID-19 pandemic. In contrast to another study ( 36 ), the effect of being a single-child on adverse emotions status was not significant in this study. The reason for this discrepancy may be due to the different regions in which the study was conducted.…”
Section: Discussioncontrasting
confidence: 99%
“…First of all, gender, grade, family size, and category of residence were taken into account regarding the general characteristics of the participants. Subsequently, being a single-child in China may lead to coping poorly with stressful situations due to the country's unique policy in this regard ( 36 ). So, we thought that might be a contributing factor and asked a question related to whether or not the student was an only child.…”
Section: Methodsmentioning
confidence: 99%
“…Such people lack awareness of the negative effects of the vaccine, and vaccine hesitancy is common in highly educated groups 24 . In addition, vaccination could reduce the probability of insomnia symptoms in our study, but this has not been identified in the studies by Alam et al 25 and Wu et al 21 . The main reasons for this discrepancy may be related to sample size, demographic structure, respondents, and contextual differences.…”
Section: Discussioncontrasting
confidence: 66%
“…From Tables 3 , 4 , 5 , our findings are also similar to those of another study from the United States, which concluded that the prevalence of anxious and depressive symptoms is higher in unvaccinated participants than in vaccinated participants 14 . A domestic study focusing on 1336 medical students showed that the risk of depression and anxiety symptoms of participants vaccinated twice decreased by 0.6–0.8 times compared with those unvaccinated 21 . The completion of vaccination had a positive influence on mental health outcomes 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the COVID-19 pandemic, as a sudden negative life event, may be the root cause of helplessness and negative attitudes in depressed patients. Furthermore, several studies have pointed out that the probability of abnormal behaviors, such as insomnia and irregular diet, has increased significantly during the pandemic ( 91 , 92 ). These studies are consistent with the Theory of Planned Behavior, which suggests that people's intentions or behaviors can be manipulated by attitudes, subjective norms, and perceived behavioral control to target behaviors ( 93 ).…”
Section: Discussionmentioning
confidence: 99%